Clonal composition and differentiation stage of human CD30+ B cells in reactive lymph nodes - Küppers, Ralf; Budeus, Bettina; Hartmann, Sylvia; Hansmann, Martin-Leo (Frontiers in Immunology, 2023)
Introduction Normal CD30+ B cells represent a distinct B-cell differentiation stage with features of strong activation. We lack an in depth understanding of these cells, because they are not present in peripheral blood and are typically very rare in reactive lymphoid organs. CD30+ B cells have been discussed as a potential precursor population for the malignant CD30+ Hodgkin and Reed-Sternberg cells in classical Hodgkin lymphoma. As CD30+ B cells can be more numerous in some cases of reactive lymphadenitis, we aimed to characterize these CD30+ B cells in terms of their differentiation stage and clonal composition, also as a means to clarify whether such CD30+ B-cell populations may represent potential precursor lesions of Hodgkin lymphoma. Methods We microdissected single CD30+ B cells from tissue sections of eight reactive lymph nodes with substantial numbers of such cells and sequenced their rearranged immunoglobulin (Ig) heavy chain V region (IGHV) genes. Results The CD30+ B cells were polyclonal B cells in all instances, and they not only encompass post-germinal center (GC) B cells with mutated IGHV genes, but also include a substantial fraction of pre-germinal center B cells with unmutated IGHV genes. In five of the lymph nodes, mostly small clonal expansions were detected among the CD30+ B cells. Most of the expanded clones carried somatically mutated IGHV genes and about half of the mutated clones showed intraclonal diversity. Discussion We conclude that in human reactive lymph nodes with relatively many CD30+ B cells, these cells are a heterogenous population of polyclonal B cells encompassing activated pre-GC B cells as well as GC and post-GC B cells, with some clonal expansions. Because of their polyclonality and frequent pre-GC differentiation stage, there is no indication that such cell-rich CD30+ B-cell populations represent precursor lesions of Hodgkin lymphoma.